Recessions and the Labor Market Returns to Cognitive and Social Skills - David E. Frisvold; Sun Hyung Kim (Institute of Labor Economics (IZA), 2024)
Although recessions negatively affect labor market outcomes, we find that individuals with greater cognitive skills have been less affected by recessions since 2000 compared to those in the 1980s and 1990s. This result occurs despite a decrease in the returns to cognitive skills over the last few decades, on average. We argue that changes in the provision of employer-paid training can help explain the relative return to cognitive skills during recent recessions due to lower training costs and enhanced labor productivity. Consistent with this, we find that firms provide more training to workers with higher cognitive skills during post-2000 recessions.
Keywords: J01; J23; J24; J31; J60; J64; 330; cognitive skills; social skills; training; recessions